EFETIVIDADE DO ACESSO ELETRÔNICO À JUSTIÇA DIRETAMENTE PELO CIDADÃO EM TEMPOS DE PANDEMIA: atermação online - Leila Maria Tinoco Boechat Ribeiro; Carlos Henrique Medeiros de Souza (TRF2, 2020)
Access to justice by electronic means, especially in the midst of the Coronavirus pandemic, in which jurisdictional entities are suspended from their face-to-face activities, becomes even more challenging to those citizens who do not yet have technologicalmeans and / or knowledge of technical assistance for its use. In this context, in which the courts implement online tapping as one of the alternatives for facilitating access to Justice by the citizen, the following problem arises: How online tapping has contributed to the effectiveness of the right of access to Justice, directly by the citizen, in this moment of COVID-19 exceptionality? The objective is to analyze online banking as a means of ensuring effectiveness to the human / fundamental right of access to Justice for citizens, directly, electronically, in the context of COVID-19, in an interdisciplinary approach of Law and New Information and Communication Technologies , going through theoretical foundations on the subject and bringing up an interview with elderly person, 65 years old, female, about her experience in filing an action, via online banking, to obtain the social assistance benefit. The study is justified by its academic and social relevance as it aims to contribute to the effectiveness of the human right of access to citizens' Justice. The adopted methodology is qualitative, regarding the problem; exploratory, as to the objectives; and bibliographic research and interview, regarding technical procedures. It is expected to favorthe effectiveness of the citizen's right to access Justice, by electronic means, in the broad terms in which it is enshrined in the national order and international diplomas